Capacity Utilization in Nepalese Sugar Industry - Bhagat, Sadan Kumar (Tribhuvan University Journal, 2010)
Under utilization of production capacity is a common issue for Nepalese manufacturing enterprises and sugar industry is no exception to this. This study mainly deals with the cause of underutilization of production capacity of Nepalese sugar mills as well as the market situation of sugar and sugarcane. Inspite of sufficient production of sugarcane, the sugar mills do not get adequate quantity and proper quality of sugarcane at right time. Almost half of the sugarcane production has no market which reveals the poor procurement system. The approved production capacity of Nepalese sugar mills is more than domestic requirement of sugar. However, the unfulfilled demand for sugar is fulfilled mainly by imported as well as smuggled Indian sugar. The capacity utilization rate of Nepalese sugar industry, which has been decreasing, dropped to 45percent in FY 2008/09. The main identified reasons are stoppage, breakdown and slow motion of machines, delay in settlement of minimum support price of sugarcane and late commencement of production season, political instability, less operation days of sugar mills and ultimately the overlook of sugar producers to utilize their full capacity of production. Measures to improve the capacity utilization rate of sugar mills have become an urgent need.